THE IMPACT OF FINANCIAL INCLUSION ON POVERTY ALLEVIATION: EMPIRICAL EVIDENCE FROM DEVELOPING COUNTRIES - Indoria, Devadutta; K. Devi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Financial inclusion consists of the different efforts and the initiatives which are considered for the improvement of the lives of the poverty-stricken population. The production of the products and services which improves the ease of accessing the products, and helps to expand upon the businesses also falls under financial integration. The study processed 64 responses from the primary quantitative data gathered from the survey conduction. With the help of survey analysis through SPSS, the identification of the views and opinions of the general public regarding such a concept can be known.